Focus group discussions on social cultural factors impacting on HIV/AIDS in Uganda. - Asiimwe, Delius; Kibombo, Richard; Neema, Stella (Makerere Institute of Social Research., 2003)
Uganda is one of the countries in Sub-Saharan Africa worst hit by HIV/AIDS, but at the same time among the few nations that have successfully stemmed the escalation of the epidemic. HIV prevalence among the adult sexually active population is estimated to have dropped from 18% in 1992 to 5% in 2001. Consequently Uganda is internationally considered a leader in responding to HIV/AIDS and many countries are keen to learn the approaches that have been used and where possible replicate them. The early political commitment spearheaded by President Museveni provided ground for mobilizing communities against HIV/AIDS, harnessing donor support and the efforts of government and civil society. These, together with the multi-sectoral approach, are some of the factors commonly cited to be behind Uganda’s success. However, it is noted that these same approaches have been applied by some other countries in Africa, but have not resulted into similar success as seen in Uganda. It is therefore believed that only country and context specific factors such as cultural norms and social patterns of people and communities could have played significant roles in Uganda’s success.
Keywords: group discussions; social cultural factors; HIV/AIDS